O lado surpreendente da queda: minha experiência com o contato improvisação - Itavo, Camila Vinhas (2020)
Contact Improvisation is analyzed from the perspective of cultural performances as a unique form of contemporary dance that emphasizes the surprising side of falling, inspired in the words of writer, anthropologist and dancer Cynthia Jean Novack (1947-1996) for whom contact improvisation “emphasizes the wildness and awkwardness of falling ”(NOVACK, 1990, p.151). The ethnographic description of this dance and its dialogical essence are presented as forms of social self-reflexivity, through the narrative, in a funneling movement of participant observation, from macro to microcosm, starting from what is given in the world to the person who writes this analysis, in search for the understanding of the relationship between the experiences provided by this performance and the multiplicity of meanings that refer to it that make it cultural performances. From what is given in the world, two testimonies available online in audiovisuals with the creator of this performance (1972), Steve Paxton, one from Juniata College, USA, in the 36th anniversary of contact improvisation, and another from the Dancing Museum, France. These two narratives are taken as sources of the ethnographic description which highlight essential performance characteristics and motivational issues which generated this dance movement. In the second chapter, the narratives which underpin the funneling of the ethnographic description are some of the writings of Steve Paxton, published by Contact Quarterly’s Contact Improvisation Sourcebook (1997), a special historical collection of this dance journal launched in 1975 as a space for reflection, debate and circulation of movement studies and experiences resulting from the performance. Along with these writings, aspects of the history of contact improvisation and the Small Dance, presented as a preparation technique for the movement, as the warming up of the perception for the dance of contact improvisation. The third chapter presents the contact improvisation class as a performance and focuses on participant observation, including my experience as a dancer, contactor, dance and contact improvisation teacher as an object of reflection on the performance load of possible transformation and transportation (Schechner, 2011) available in the classroom and at the jam sessions.